An impact of CYP3A4 *1B polymorphism on rifampicin metabolism - Poludenko, H. O.; Antonenko, P. B. (Journal of Education, Health and Sport, 2017)
Until now, the enzyme systems responsible for biotransformation of the antituberculous drug rifampicin remain unknown. The aim of research was an investigation of the candidate enzymes involved in the biotransformation of rifampicin using the computer system PASS and an experimental study concerning the effect of the polymorphism of the biotransformation gene CYP3A4 *1B on the level of rifampicin in the blood of patients with pulmonary tuberculosis (РTB). The probability (Pa) of certain pharmacological activity and the effect on putative enzyme systems of the human body of rifampicin has been calculated by the PASS method. Polymerase chain reaction revealed the polymorphism of the CYP3A4 *1B gene among healthy volunteers as well as patients with РTB. With a high degree of probability, according to PASS calculations, it was predicted that rifampicin undergo metabolism with the CYP3A4 enzyme - probability (Ra) were 0.891. According to the genotype CYP3A4 *1B, 95.3% of the healthy donors carried a homozygous wild-type gene (i.e., had high enzymatic activity) - AA genotype; the rest 4.7% - were carriers of the heterozygous AG genotype (moderate enzyme activity).The polymorphism of CYP3A4 *1B genotypes and alleles in the south-west of Ukraine was close to the results obtained in European countries. 91.4% and 8.6% of the patients with РTB had AA and AG genotype, correspondently. Thus, among the patients with РTB, the AG genotype was more often observed than among healthy volunteers. There was no significant difference in rifampicin concentration among РTB-patients concerning CYP3A4 * 1B polymorphism.